2009
DOI: 10.3852/08-230
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the falcate-spored graminicolous Colletotrichum and a description of six new species from warm-season grasses

Abstract: Species limits in the fungal genus Colletotrichum are traditionally distinguished by appressorial and/or conidial morphology or through host plant association, but both criteria are criticized for their inability to resolve distinct taxa. In previous research eight novel falcate-spored Colletotrichum species were identified from graminicolous hosts using multilocus molecular phylogenetic analysis. In the present work formal descriptions and illustrations are provided for six of the new taxa: C. hanaui sp. nov.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 21 publications
2
84
0
3
Order By: Relevance
“…Concerns were expressed occasionally when using ITS sequence data alone for the identification of Colletotrichum spp (2). Crouch et al reported a high error rate (86%) for comparing ITS sequence data within the C. graminicola species complex (6). Similarly, more than 86% evolutionary divergence was noted from type species of C. gloeosporioides for the analysis of 343 ITS sequences (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerns were expressed occasionally when using ITS sequence data alone for the identification of Colletotrichum spp (2). Crouch et al reported a high error rate (86%) for comparing ITS sequence data within the C. graminicola species complex (6). Similarly, more than 86% evolutionary divergence was noted from type species of C. gloeosporioides for the analysis of 343 ITS sequences (3).…”
Section: Discussionmentioning
confidence: 99%
“…The epitypification of this fungus is important, as the type strain might have been lost or might be in poor condition (12,29). Certain positive developments in the epitypification has helped to solve many taxonomic problems and the understanding of species, genera, families, or orders of this group of fungi (6,11,12,25,29). Presently, Colletotrichum spp.…”
Section: Discussionmentioning
confidence: 99%
“…The ascomycete genus Colletotrichum (Glomerellaceae, Sordariomycetes) contains many well-known plant pathogens that cause anthracnose and a range of diseases worldwide on economic crops and ornamental plants (Crouch & Beirn 2009, Crouch et al 2009, Damm et al 2009, Hyde et al 2009a. They are amongst the most important plant pathogens as they cause latent or quiescent infections at the pre-harvest and post-harvest stages (Sutton 1992).…”
Section: Evolution Of Species Criteria In Colletotrichummentioning
confidence: 98%
“…On the other hand, it also has been determined that there are many sequences deposited in GenBank incorrectly named Colletotrichum species Crouch et al 2009a;Phoulivong 2011), and the question has been raised as to the use of nucleotide data in species identification. As a consequence, several researchers (Cannon et al 2008;Crouch and Beirn 2009;Crouch et al 2009b;Damm et al 2009) have made efforts directed towards the goal of revising the genus with the use of epitypification. Cai et al (2009) introduced a polyphasic approach to deal with species concepts in the genus, and this hypothesis was also suggested as appropriate for the plant pathogenetic Colletotrichum .…”
Section: Problems Of Identification Of Colletotrichum Endophytes Usinmentioning
confidence: 98%